Shear Deformation Behavior Of Hybrid Composite (GFRP/CFRP) - Ab Ghani, Ahmad Fuad; Mahmud, Jamaluddin (WILEY-VCH Verlag GmbH & CO., 2017)
This paper presents the findings of shear deformation and behavior of hybrid composites consisting of unidirectional glass fiber reinforced polymer (GFRP) and carbon fiber reinforced polymer (CFRP) under shear loading. The use of hybrid composites for aeronautic and marine applications which improve the modulus of elasticity of glass fiber reinforced polymer while reducing costs of carbon has motivated the study on shear for hybrid composites. Several tests of 10 8 and 45 8 off axis shear have been performed to characterize shear deformation of unidirectional carbon fiber reinforced polymer, unidirectional glass fiber reinforced polymer and three different orientations and layups of glass fiber reinforced polymer/carbon fiber reinforced polymer hybrid composite. The shear strain measurements have been conducted with the conventional method of rosette strain gauge and with digital image correlation (DIC) technique using the opensource platform Ncorr. The values of shear modulus obtained from experiment for glass fiber reinforced polymer and carbon fiber reinforced polymer are quite close with the manufacturers’ data sheet while the improvement of the shear modulus of the hybrid corresponds to the amount of carbon content in hybrid composition, similar to literature findings. Shear strain values measured for off axis shear test using rosette strain gauge are consistent with the results from digital image correlation technique but slightly differ with each other for hybrid composites due to full field measurement contour and complex shear deformation behavior for hybrid composite.